2024
DOI: 10.1002/cm.21870
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure expansion microscopy (U‐ExM) of mouse and human kidneys for analysis of subcellular structures

Ewa Langner,
Pongpratch Puapatanakul,
Rachel Pudlowski
et al.

Abstract: Ultrastructure expansion microscopy (U‐ExM) involves the physical magnification of specimens embedded in hydrogels, which allows for super‐resolution imaging of subcellular structures using a conventional diffraction‐limited microscope. Methods for expansion microscopy exist for several organisms, organs, and cell types, and used to analyze cellular organelles and substructures in nanoscale resolution. Here, we describe a simple step‐by‐step U‐ExM protocol for the expansion, immunostaining, imaging, and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 112 publications
0
0
0
Order By: Relevance
“…Here, we demonstrated that the duration of PFA fixation and long- term storage at -80°C do not significantly impact the degree of retinal tissue expansion, achieving approximately 4x isotropic expansion ( Figure 2 ). This observation aligns with the recent reports that applied U-ExM to PFA-fixed frozen and formalin-fixed paraffin-embedded mouse tissues [20, 28]. Notably, our results showed that U-ExM enabled super-resolution imaging of archival samples that had been cryopreserved for over a decade, providing comparable imaging quality to that obtained from fresh samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we demonstrated that the duration of PFA fixation and long- term storage at -80°C do not significantly impact the degree of retinal tissue expansion, achieving approximately 4x isotropic expansion ( Figure 2 ). This observation aligns with the recent reports that applied U-ExM to PFA-fixed frozen and formalin-fixed paraffin-embedded mouse tissues [20, 28]. Notably, our results showed that U-ExM enabled super-resolution imaging of archival samples that had been cryopreserved for over a decade, providing comparable imaging quality to that obtained from fresh samples.…”
Section: Discussionsupporting
confidence: 90%
“…Based on these findings, we assumed that the region with glutamylation outside the tubulin axoneme is equivalent to the CC and measured the length and width of each compartment of the PSC axoneme ( Figure 3E ). As previously reported for other cell types [27, 28], the length of the MC was significantly longer than that of the daughter centriole (DC) in each photoreceptor subtype. More interestingly, cone photoreceptors had notably longer BBs than rods (Rod DC, 269.71 ± 24.00 μm; Cone DC, 357.27 ± 37.26 μm; Rod MC, 372.06 ± 55.22 μm; Cone MC, 465.84 ± 40.58 μm; Figure 3F ).…”
Section: Resultssupporting
confidence: 81%